EFL Teachers’ perceptions towards influential factors on the application of blended learning in high schools : - Trần, Nguyễn Vạn Thông (Trường Đại học Cần Thơ, 2019)
The use of Blended learning in education has advanced significantly since the late 1990s. At present, it is much unknown about the use of Blended learning in high school in Vietnam. This thesis investigates the perceptions of English as Foreign Language (EFL) teachers towards factors affecting the application of Blended learning in Vietnamese high schools. The research aim is to (1) identify EFL teachers’ perceptions of factors affecting the application of Blended learning and (2) find out the most promoting and challenging among these factors on the application of Blended learning. A mixed-methods approach was conducted, which involved quantitative and qualitative data collection from 45 EFL teachers (n=45). The data was collected via questionnaire and interview. The participants are 45 teachers from high schools in the Mekong Delta. The findings indicate factors affect most the application of Blended learning and determine supports needed by teachers to facilitate the application of Blended learning.